Developing GUI and tools for Maya software B - Ayesha Shakya (2013)
As part of the curriculum of the Bachelor of Engineering (Information Engineering & Media) in Nanyang Technological University, the student had to undertake her Final Year Project, titled ‘Developing GUI and tools for Maya software’. The main objective of the project was to create a graphical user interface which reorganizes and simplifies the process of creating smoke in Autodesk Maya. Maya’s current user interface is vast and extensive and, for a novice user, it could appear complex and difficult to navigate. That being said, smoke can be created within Maya through multiple methods, depending on the user’s preference. With a wide variety of options and techniques available to obtain the needed effects, the original interface can appear complicated and extensive. With the present options and complexities involved in creating smoke, the project aims to use the Python programming language and the Qt application development framework to create the modified GUI application with the aim of making the existing user interface more user-friendly and intuitive to use.